A Review on The Compressive Strength and Workability of Concrete with Agricultural Waste Ash as Cement Replacement Material - Razeman N.A.; Itam Z.; Beddu S.; Izam N.S.M.N.; Ramli M.Z.; Syamsir A.; Mohamad D.; Kamal N.L.M.; Usman F.; Asyraf M.R.M. (Institute of Physics, 2024)
Concrete is commonly used as a construction material because of the important properties is broadly utilized as development materials within the development segment. Unfortunately, the component of cement within the concrete results in many side-effects such as affecting the environment. Therefore, this paper presented the review of essential to seek out an alternative materials which may be utilized as cement replacement materials by reutilizing agricultural waste ash. Selected agricultural waste ash which are Palm Oil Fuel Ash (POFA), Rice Husk Ash (RHA), Groundnut Shell Ash (GSA), Sugarcane Bagasse Ash (SBA) and Oyster Shell Powder (OSP) were review in terms of their compressive strength and slump height of the mixture. The treated palm oil ash which is going to be used as partial cement replacement material for the proper design mix and optimal ash replacement. The replacement percentage of palm ash in the concrete were set at 10%, 20%, and 30% by weight with the optimal replacement ratio of the supplementary cementitious content. Palm Oil Fuel Ash (POFA) is a material that having sufficient requirements to be a good pozzolana and cementitious material according to ASTMC618 in terms of chemical composition. POFA is a material that consists high silica contents. By having more silica contents, it will help to improve the properties, in particular its compressive strength, bond strength, and abrasion resistance. After conducting several research, it was concluded that the optimal replacement for POFA is 20% and it is better to have finer POFA. POFA also proved some of the important properties is the CO2 emissions would be reduce. 2023 Institute of Physics Publishing. All rights reserved.